Effect of body mass index in acute respiratory distress syndrome. (January 2016) - Chiumello, D.; Colombo, A.; Algieri, I.; Mietto, C.; Carlesso, E.; Crimella, F.; Cressoni, M.; Quintel, M.; Gattinoni, L.
Abstract: Background: Obesity is associated in healthy subjects with a great reduction in functional residual capacity and with a stiffening of lung and chest wall elastance, which promote alveolar collapse and hypoxaemia. Likewise, obese patients with acute respiratory distress syndrome (ARDS) could present greater derangements of respiratory mechanics than patients of normal weight. Methods: One hundred and one ARDS patients were enrolled. Partitioned respiratory mechanics and gas exchange were measured at 5 and 15 cm H2 O of PEEP with a tidal volume of 6–8 ml kg −1 of predicted body weight. At 5 and 45 cm H2 O of PEEP, two lung computed tomography scans were performed. Results: Patients were divided as follows according to BMI: normal weight (BMI≤25 kg m −2 ), overweight (BMI between 25 and 30 kg m −2 ), and obese (BMI>30 kg m −2 ). Obese, overweight, and normal-weight groups presented a similar lung elastance (median [interquartile range], respectively: 17.7 [14.2–24.8], 20.9 [16.1–30.2], and 20.5 [15.2–23.6] cm H2 O litre −1 at 5 cm H2 O of PEEP and 19.3 [15.5–26.3], 21.1 [17.4–29.2], and 17.1 [13.4–20.4] cm H2 O litre −1 at 15 cm H2 O of PEEP) and chest elastance (respectively: 4.9 [3.1–8.8], 5.9 [3.8–8.7], and 7.8 [3.9–9.8] cm H2 O litre −1 at 5 cm H2 O of PEEP and 6.5 [4.5–9.6], 6.6 [4.2–9.2], and 4.9 [2.4–7.6] cm H2 O litre −1 at 15 cm H2 O of PEEP). Lung recruitability was not affected by the body weight (15.6 [6.3–23.4], 15.7 [9.8–22.2], and 11.3 [6.2–15.6]% for normal-weight, overweight, and obese groups, respectively). Lung gas volume was significantly lower whereas total superimposed pressure was significantly higher in the obese compared with the normal-weight group (1148 [680–1815] vs 827 [686–1213] ml and 17.4 [15.8–19.3] vs 19.3 [18.6–21.7] cm H2 O, respectively). Conclusions: Obese ARDS patients do not present higher chest wall elastance and lung recruitability.